Provisional Vs Dual Stenting of Left Main Coronary Artery Bifurcation Lesions - Aftab Ahmed Solangi, Nasrullah, Jalaludin, Amir Jamil, Omer Aslam (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The primary LMCA stenting methods used nowadays consist of single stent (provisional), and two stent (T and protrusion, and double kissing crush DK crush, culotte, or classic crush). The optimal technique for bifurcation lesion treatment for the patients present with distal ULMCA disease is still unclear and not much is known about the best course of action and the clinical outcomes following various PCI techniques for ULMCA bifurcations in Pakistan. Objective: To investigate the midterm (3-year) outcomes related to the provisional stenting compared to two-stenting technique for the bifurcations of ULMCA undergoing the percutaneous coronary intervention. Methodology: A single-center retrospective, non-randomized cohort study was conducted during the period from March 2021 to August 2022 including all the consecutive LM bifurcation lesions. The patients attending Punjab Institute of Cardiology, Lahore were divided into two groups, depending upon the treatment received. One group underwent PCI with provisional stenting technique while the other underwent 2-stent PCI. The groups were compared for procedural success and 3-year clinical outcomes. Data was analyzed using SPSS. Results: The success rate of left main bifurcation angiography was comparable between both the techniques (2-stent 93.6 % vs. Provisional 92.1 %, P = 0.62). MACE rates were comparable between groups at 1, 2, and 3 years (PS 3.0 % vs. Dual stent 2.4 %, p = 0.75 at 1-year, PS 4.8 % vs. Dual stent 8 %, p = 0.26 at 2-years, and PS 10.2 % vs. Dual stent 12 % at 3-years, p = 0.62). Conclusion: Two stenting strategy was linked to same rates of MACEs at the 3-year duration in comparison to the single stenting technique (PS 10.2 % vs. 2-Stent 12 %, p=0.62) and both the dual and single provisional stent techniques have comparable angiographic success rate for LM bifurcation lesions.